2018
DOI: 10.3389/fphys.2018.01434
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage Stiffness Effect on Foot Biomechanics of Chinese Bound Foot: A Finite Element Analysis

Abstract: The purpose of this study is to investigate the effect of cartilage stiffness on inner foot biomechanics of Chinese bound foot while balanced standing using finite element method. A three-dimensional FE model of bound foot involving 28 bones, 72 ligaments, 5 plantar fascia, cartilages, and encapsulated soft tissue was constructed and validated. To conduct the sensitivity analysis of cartilage stiffness, the incremental Young’s modulus of 1, 5, 10, and 15 MPa were assigned to the cartilage. 25% of the body weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…It can not only repeat and change various stress areas and directions for complex stress analysis, but also keep the physical properties of the model constant, which can make up for the shortcomings of in vitro cadaveric experiments and animal experiments. It is widely used in biomechanical research [ 36 , 37 ]. This study has shown that the finite element method can well explore chevron osteotomy, to explore the effect of different degrees of extrapolation on metatarsal stress.…”
Section: Discussionmentioning
confidence: 99%
“…It can not only repeat and change various stress areas and directions for complex stress analysis, but also keep the physical properties of the model constant, which can make up for the shortcomings of in vitro cadaveric experiments and animal experiments. It is widely used in biomechanical research [ 36 , 37 ]. This study has shown that the finite element method can well explore chevron osteotomy, to explore the effect of different degrees of extrapolation on metatarsal stress.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is important to consider the effect of pressure-time integral when considering the potential for injuries such as stress fractures, it is also important to consider the force-time integral. The force-time integral offers valuable insight to evaluate pathomechanics associated with overuse injuries in specific foot regions along the area under stress [29, 30]. For the force-time integral, the PP had the higher force-time integral at the SATM and FM area while the AP had a higher force-time integral at the BT and metatarsal areas.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional biomechanical experiments (such as animal experiments, in vitro cadaveric specimens, etc.) often cannot fully reflect the real biomechanical changes of internal bones, but three-dimensional finite element analysis (FEA) can simulate the complex mechanical environment in a mathematical form and provide internal mechanical information ( 18 , 19 ). FEA facilitates the measurement of external forces and the analysis of internal stresses during the experimental investigation and provides a better understanding of the cat's special landing mechanism.…”
Section: Introductionmentioning
confidence: 99%